Attitudes to and use of lubrication during heterosexual sex by students at Wits University - John, Victoria (My University, 2021)
This research explores the attitudes to and use of lubrication during heterosexual sex by Wits University students in Johannesburg in the context of Sexual and Reproductive Health and Rights (SRHR) organisations and researchers finding that wetter sex is safer sex. Coupled with lubrication, sex is made safer for three reasons: it reduces condom usage failure, reduces the chance of vaginal lesions and increases pleasure. But introducing the topic of lubrication seems a concept out of reach for many education and public health sites in South Africa. The Abstain, Be Faithful, Condomise (ABC) approach to safe sex has been employed for decades at sites of formal sex education and shifts from its largely conservative positions are not always welcome: the introduction of the Comprehensive Sexualities Education (CSE) syllabus into sex education at schools triggered hostilities among parents and school bodies across the country. The ABC approach has been called into question, however, by research showing that denying all-gendered pleasure – including lubrication’s role - a place at the table of these discussions results in missed opportunities to affect behavioural change and safer sex. Much research has been done on the biomedical benefits of introducing lubrication during sex. Lubrication enhances the environment for successful condom use and safer sex: enough wetness to reduce the chance of friction that can cause condom failure as well as lesions in the vagina both of which increase the risk of exposure to STIs. But speaking about lubrication cannot take place without speaking about sexual pleasure for both men and women because wetness during sex is a result of sexual arousal by men, and women in particular. The first step in understanding how resistant South Africans would be to the policy of using lubrication with condoms, however, would be establishing what exactly their understanding, and experience, is of lubrication, pleasure and pain. An anonymous survey invited students to answer questions about why and how they understand sex, pleasure, communication with their partner/s and their experience of sex education. They were asked about the mechanics of sex: their condom use and failure, dryness during sex, their reasons for using – or not using – lubrication, pain during sex and its opposite experience: pleasure. The data showed a prevalence of dryness during sex which respondents said was one of the main causes of condom failure. Apart from the risk of exposure to STIs presented by condom failure, dryness was also one of the main causes of pain during sex. This is significant because respondents indicated that the opposite sensation - pleasure - was one of the main reasons respondents had sex. Despite this, a large proportion of respondents had not used lubrication before and their responses indicated poor knowledge of its benefits. This is likely due to, in part, the sex education many of them received at schools which did not mention lube or pleasure. The data were also analysed according to gender because of the difference in how, biologically, men and women experience sex – like who produces natural lubrication - but also because of the powerful influence that gendered identities, beliefs and biases have on sexual experiences. The data revealed that respondents’ experiences of dryness, their perceptions of reasons for condom failure, and pain during sex, among other experiences, were different depending on their gender. The data showed that men and women perceive and understand sex in different ways and, because of social conditioning around this, do not adequately communicate these experiences to their partners. This can exacerbate condom failure and pain during sex. This research therefore recommends more comprehensive, gender-inclusive, sex education at schools and other institutions that explicitly addresses lubrication and its benefits as well as pleasure. It also recommends that free lubrication be far more accessible to South Africans. This research can reliably be used to inform campaigns by SRHR organisations to encourage South Africans to use lubrication to ensure more pleasurable and safer sex
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts in Development Studies to the Faculty of Humanities, School of School of Sociology, University of the Witwatersrand, 2021